A novel taxane, difluorovinyl-ortataxel, effectively overcomes paclitaxel-resistance in breast cancer cells. (28th October 2020) - Rong, Dade; Wang, Changwei; Zhang, Xiaomei; Wei, Yanli; Zhang, Mingming; Liu, Daiyuan; Farhan, Haider; Momen Ali, Saleh Abdul; Liu, Yanbin; Taouil, Adam; Guo, Wanrong; Wang, Yican; et al.
Abstract: Paclitaxel (PTX) is widely used to treat breast and ovarian cancers, but innate and acquired resistance often compromises its applications. The objective of this study was to screen new-generation taxanes for their efficiency against both PTX-sensitive and PTX-resistant breast cancer cells. From twelve compounds, difluorovinyl-ortataxel (DFV-OTX) displayed potent cytotoxic activities against both PTX-sensitive and PTX-resistant breast cancer cells. Moreover, DFV-OTX effectively induced tubulin/microtubule polymerization and G2/M phase arrest, leading to apoptosis in both PTX-sensitive and PTX-resistant cancer cells. Molecular docking analysis showed that DFV-OTX possesses unique hydrogen-bonding and van der Waals interactions with β-tubulin. LC-MS/MS analysis also demonstrated that the intracellular drug amount of DFV-OTX was lower than that of PTX, which would be critical to overcome PTX-resistance. Furthermore, DFV-OTX exhibited clear efficacy in the MCF-7R and MDA-MB-231R tumor xenografts in mouse models. Taken together, our results demonstrate that the novel taxane, DFV-OTX, can effectively overcome PTX-resistance in MDA-MB-231R cells, wherein the drug resistance was attributed to ABCB1/ABCG2 upregulation and a distinct mode of action in MCF-7R cells. Our results strongly indicate that DFV-OTX is a promising chemotherapeutic agent for the treatment of PTX-resistant cancers. Highlights: DFV-OTX exhibited effective cytotoxicity against PTX-resistant breast cancer cells. DFV-OTX had unique hydrogen-bonding and vdW interactions with β-tubulin. DFV-OTX showed lower intracellular drug level but higher cytotoxicity than PTX. DFV-OTX showed potent therapeutic efficacy against PTX-resistant tumor xenografts.